OUTCOMES AND CLINICAL FEATURES OF PEDIATRIC AML AT ADDIS ABABA TERTIARY HOSPITAL: A RETROSPECTIVE CROSS-SECTIONAL STUDY - Berhanu , Mesfin A; Assefa , Solomon G (American Research Journal of Nursing and Health Sciences (ARJNHS), 2024)
Acute Myeloid Leukemia (AML) in pediatric populations accounts for 15-20% of all acute leukemias, with recent studies from African cancer registries indicating a prevalence of 20-25% (de Rooij et al., 2015; Molyneux et al., 2017; Kassahun et al., 2020). However, comprehensive data on pediatric AML incidence in Ethiopia remains limited. AML's etiology involves a combination of genetic and acquired/environmental risk factors, though the exact age at presentation varies. A review of literature shows a median presentation age of 7.4 years, with ranges from 8 months to 15.8 years (Viana et al., 2003), and variations in mean and median ages across studies (Ghafoor et al., 2020; Van Weelderen et al., 2021). Clinical characteristics, such as malnutrition prevalence, initial white blood cell counts, and morphological subtypes, also vary widely. For instance, a Brazilian study reported a malnutrition rate of 29.4%, with a median initial white blood cell count of 23.3×10^3/mm^3, and the most frequent morphologies being M2 (35%) and M3 (22%) (Viana et al., 2003). This study aims to fill the gap by evaluating the clinical features and induction outcomes of pediatric AML patients at a tertiary referral hospital in Addis Ababa, Ethiopia, using a retrospective cross-sectional approach.